Pengembangan Sistem Oracle Forms untuk Optimisasi Proses Penjualan di PT.XYZ - G.A, Ambrosius Ludang; Mailoa, Evangs (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research focuses on the development of an efficient sales system for PT. XYZ a retail company in Indonesia. The company faces challenges in its sales processes due to the lack of efficiency in the manual system, which is susceptible to errors. The research aims to optimize the sales process by utilizing Oracle Forms 10g and implementing the Rapid Application Development (RAD) methodology to ensure timely solutions. The developed system demonstrates a significant improvement in efficiency, accuracy, and speed. The use of Oracle Forms and SQL Developer simplifies data entry and management processes, while the implementation of List of Values (LOV) reduces errors and enhances data consistency. Furthermore, the system provides real-time insights into sales performance, enabling better decision-making and strategic planning for the company.